PEMBELAJARAN BERBASIS SIRAH NABAWIYAH DALAM UPAYA PEMBENTUKAN KARAKTER SISWA KELAS V DI SD ISLAM CENDEKIA MUDA - Azizah, Auria Regina Nur; Ramdhan, Dadan F; Mahmud, Muhammad Rifqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the lack of research discussing the Sirah Nabawiyah integrated with subjects, especially at the elementary school level. The purpose of this study was to determine the planning, learning process, assessment, and supporting and inhibiting factors of Sirah Nabawiyah-based learning in character building at SD Islam Cendekia Muda. This study uses a qualitative approach with a descriptive method. Data collection techniques include interviews, observation, and documentation. The research subjects consist of the principal, fifth-grade teachers, students, and parents. Data analysis is carried out through data reduction, data presentation, and conclusion drawing. The results of the study show that: (1) The learning plan has unique characteristics because it integrates the Merdeka Curriculum with the God-Centered Education (GCE) approach and includes character indicators from the phases of the Prophet's life that are integrated into all subjects; (2) The implementation of Sirah Nabawiyah-based learning in schools reflects the integration of contextual approaches, character education, and Islamic spirituality, which are carried out comprehensively by teachers and students and fully supported by the school environment and parents; (3) Assessment is carried out holistically through observation of students' attitudes, participation, and behavior; (4) Supporting factors include teacher commitment, support for the God Centered Education curriculum, and parental involvement, while inhibiting factors include time constraints and differences in student abilities; (5) Sirah Nabawiyah-based learning can be said to have succeeded in shaping students' character towards noble morals, although the full effectiveness of this learning still needs to be improved through deepening of Sirah material, increasing teacher competence, and continuity of cooperation between the school and families.